Jan Patočka and Charta 77 as a Philosophical Problem - Bęben, Dariusz (Folia Philosophica, 2017)
Patočka’s philosophical work is very extensive; therefore, it is necessary to pay special attention to each area of his interest. It seems that the most important thing in his philosophical heritage is his effort to bridge political and philosophical thought. The aim of this article is to describe the influence of the philosophy of Jan Patočka on the Charter 77 programme. His role was revealed mainly in providing Charter 77 with the moral and existential context.